Food security measures during uncertain climatic conditions in Nigeria (2009)
Food security is a function of a few variables such as technological input, capital, government policies and environmental (climate) factors. Good control of all these dependent variables except the last, and the thorough understanding of the last can take the nation to food security level. Possible ways of controlling the first three variables (technological input, capital, government policies) are suggested. To have thorough understanding of the climate factors, time series analysis of climate variables precisely temperature and precipitation data in twelve locations covering the various climatic belts of Nigeria were carried out. Nigeria rainfall has a usual zonal pattern and the vast majority of precipitation falls within a well-defined period. The coastal stations received more rainfall than the inland locations. The northern locations received less rainfall than southern locations. The onset period for the northern stations is May/June while the cessation period is September/October. The southern stations have April as their onset month while October is their cessation month. The southern stations have two peaks of rainfall in June/July and September. A period when rainfall ceases within the wet season exists in the south, and is referred to as ‘August break’. The northern stations have only one peak, which is in August. Annual trend of precipitation is positive in most of the southern stations while it is negative in most northern stations. At the ninety-nine percent confidence limits, all the stations have mean annual rainfall close to or within the limits except during El Nino Southern Oscillation (ENSO) years. Harmonic analysis reveals 3 to 4 and 7-8 years inter-annual cycle of precipitation which correspond to the warm and cold ENSO cycle. Temperature has a bimodal variation through the twelve months in a year. The two maxima occur in March/April/May and October/November while the minimum is in July/August. Annual temperature trend is positive (small slope) in some stations while it is negative in some not necessarily depending on the position.